2019
DOI: 10.18485/esptoday.2019.7.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Test-Taking Strategies to EFL Student Readers with Different Language Proficiencies: An Empirical Reassessment

Abstract: This study investigated the effect of teaching test-taking strategies to EFL student readers with different levels of reading proficiency (i.e. high and low). Two groups of undergraduate non-English majors joined an eight-week experiment. One served as the treatment group (TG) which learned test-taking strategies to tackle English reading test tasks, while the control group (CG) received no strategy instruction. The pretest and posttest reading performances of all the participants from the TG and CG were quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Similarly, Alzubi et al (2019), experimenting with a reading strategy training through smartphones, confirmed that the training promotes EFL learners' autonomy; however, its effect on reading performance was not significant. In the field of reading test taking, Lee (2019) confirmed that both high and low proficiency Taiwanese EFL students in her study obtained better scores after undergoing test-taking strategy training. She further elaborated that cognitive strategies (lexicogrammatical, sentence-based, and reading comprehension strategies) were employed more significantly than technical strategies (including metacognitive (time calculation for reading speed adjustment) and compensation strategies (skipping difficult questions, making educated guesses) and postulated that the latter may be mostly used by weak readers who were struggling with reading comprehension.…”
Section: Reading Strategy-based Instructionsupporting
confidence: 55%
“…Similarly, Alzubi et al (2019), experimenting with a reading strategy training through smartphones, confirmed that the training promotes EFL learners' autonomy; however, its effect on reading performance was not significant. In the field of reading test taking, Lee (2019) confirmed that both high and low proficiency Taiwanese EFL students in her study obtained better scores after undergoing test-taking strategy training. She further elaborated that cognitive strategies (lexicogrammatical, sentence-based, and reading comprehension strategies) were employed more significantly than technical strategies (including metacognitive (time calculation for reading speed adjustment) and compensation strategies (skipping difficult questions, making educated guesses) and postulated that the latter may be mostly used by weak readers who were struggling with reading comprehension.…”
Section: Reading Strategy-based Instructionsupporting
confidence: 55%
“…Takallou et al (2015) demonstrated that strategy training had a considerable positive effect on students' performance on the English section of University Entrance Examination test. Similarly, after the interventions carried out in the experiments described by Lee (2019aLee ( , 2019b, the experimental groups, which had received strategy training, significantly outperformed the control groups in the posttests. Other researchers - Ghafournia and Afghari (2013) recommend students be taught the relevant strategies, similarly to Ghafournia (2013) who claims high-proficient testees use different strategies from lower-proficiency ones and that "strategic based instruction should be used to improve the process of language learning" (p. 94).…”
Section: International Journal Ofmentioning
confidence: 86%
“…Three of its four categories are related to the three test tasks she used, the fourth category, technical approaches, contains strategies that correspond to Cohen and Upton's test-management and test-wiseness strategies. The author used her survey in her subsequent studies (Lee, 2019a andLee, 2019b).…”
Section: Questionnaires and Inventoriesmentioning
confidence: 99%
See 2 more Smart Citations